PELATIHAN PENGEMBANGAN KEGIATAN LITERASI KURIKULUM MERDEKA BELAJAR MERDEKA BERMAIN DI TK AISYIAH BUSTANUL ATHFAL 14 KECAMATAN KARANGPILANG SURABAYA - Hasiana, Isabella; Aisyah, Aisyah (LPPM Institut Pendidikan Nusantara Global, 2023)
The use of the concept of independent learning in education provides great potential for the development of better education in Indonesia. Through community service activities, the Early Childhood Education Teacher Education Study Program (PG-PAUD) provides training to encourage and train PAUD teachers at TK Aisyiyah Bustanul Athfal 14 Surabaya to be able to have knowledge and skills in planning literacy-based learning as part of the implementation of independence Study. This community service activity is in the form of literacy-based learning preparation training as an implementation of the independent learning curriculum for Aisyiyah Bustanul Athfal 14 Surabaya Kindergarten teachers. The use of the concept of independent learning in education provides great potential in the development of better education in Indonesia. Through independent learning, students are expected to be able to have Aisyiyah Bustanul Athfal 4C that is competencies, namely communication, creativity, collaboration and critical thinking. By having these 4C competencies, children will not only memorize lessons, but will be able to create new things or new innovations for Indonesia in all fields, have social skills to work together and have character, ethics and normalcy.